Uses and mechanisms of apnoeic oxygenation: a narrative review. (19th February 2019) - Lyons, C.; Callaghan, M.
Summary: Apnoeic oxygenation refers to oxygenation in the absence of spontaneous respiration or mechanical ventilation. It has been described in humans for over half a century and has seen a resurgence in interest given its potential to delay oxygen desaturation during airway management, especially with the advent of high‐flow nasal cannulae. This narrative review summarises our current understanding of the mechanisms of gas exchange during apnoeic oxygenation and its diverse range of clinical applications, including its use at induction of anaesthesia and for the facilitation of 'tubeless anaesthesia'. Additional discussion covers use in critical care, obese, obstetric and paediatric sub‐populations. The article also highlights current research efforts aiming to enhance the evidence base for the use of this technique.